MODELLING OF THERMAL PROCESSES OF THE SOLAR COLLECTOR - Alexei Ivanovich Yurov; Eugene Nikolaevna Pertsevaya (Современная наука и инновации)
In article creation of mathematical model and its discrete analog for the further decision with use of numerical methods is considered. To determine the dynamic characteristics of the control object on the selected spatial modes using numerical models.